PENGARUH DISKONFIRMASI POSITIF (KINERJA MELEBIHI HARAPAN), KEPUASAN DAN LOYALITAS TERHADAP INFORMASI DARI MULUT KE MULUT (STUDI PADA PENGUNJUNG TAMAN KOTA DI SURABAYA) - Khoirunnisa Barmawi (Journal of Business & Banking, 2012)
Information which is transferred by means of words of mouth has become very influential factor especially when the company tries to create the society trust on the company services. This study attempts to find out people experiences of rating the positive disconfirmation (performance more than expectation) and visitors satisfaction after visiting the city parks, as well as to see to what extent the loyalty influences the visitors in city parks which is then subsequently to induce word of mouth implementation. This research uses questionnaires for gathering the data with sampling technique use judgment sampling by considering that the respondents who visited in 5 city parks are Flora Park of Kebun Bibit, Prestasi Park, Sulawesi Park, Bungkul Park, Mundu Park. They came in the last time when visiting the park minimally 3 months before this research was done. They had visited the park minimal > 2 times. The 15 years old is the minimal. Therefore, the sample taken in this research is of 200 samples as city park visitors in Surabaya. This was reduced into 5 city parks in Surabaya. It was proved that there was disconfirmation (performance more than expectation) has a positive and significant influence toward satisfaction. Satisfaction has also a significant effect toward loyalty and, in turn, the loyalty has a significant effect toward word of mouth.